Challenges in e-tendering implementation in Ministry of Youth and Sports Malaysia / Ahmad Zamie Azis - Ahmad Zamie, azis (2020)
The Ministry of Youth and Sport, like most ministries in Malaysia, tenders its projects through the traditional paper-based tendering process, which has many weaknesses, including bureaucracy and lack of transparency. In 2008, e-Tender was one of government incentive under e-Government application was introduced to replace manual tendering system in public agencies to systematic procurement which using internet as platform of transaction. Like any other transition project, implementation of e-tender in Ministry of Youth and Sport, is associated with several challenges. This research aims to explore the challenges facing the implementation of the e-tender system in the Ministry of Youth and Sport and to propose some recommendations that should be adopted. 18 challenges are highlighted based on survey conducted, and 5 categories; Lack of System Integration and Standardization, Immaturity of system, Lack of supplier’s preparation, End User Resistance, Technology Risk / Technical Readiness and Top Management Support are identified by literature. 65 respondents are were involve with this study to examine and ranked with respect to their importance. This study also intentions to understand relations of implementation of e-tender with procurement performance and did it give an affect the procurement performance of the Ministry of Youth and Sports.